2006
DOI: 10.1029/2006gc001247
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric imaging of crustal magma storage beneath the Mesozoic crystalline mountains in a nonvolcanic region, northeast Japan

Abstract: [1] Mesozoic crystalline mountains (Iide Mountains) in a nonvolcanic region of the Northeast Japan Arc were imaged by wide-band magnetotelluric soundings. A two-dimensional model shows that an anomalous conductive body (<10 Wm) is clearly visible beneath the Iide Mountains. The conductor widens with increasing depth and extends from the near-surface down to the base of the crust and perhaps into the upper mantle. The location of the conductive body correlates with high-temperature hot springs with high 3 He/ 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The distribution of conductor C6 and its resistivity (1 to 10 Ωm) are also consistent with the results of previous studies (Ogawa et al 1986;Ogawa 1987b). Recent wideband magnetotelluric profile measurements with site spacings of several kilometers have yielded more detailed images of the locations and depths of these conductors, although those images were limited to two-dimensions (Mitsuhata et al 2001;Ogawa et al 2001;Umeda et al 2006;Mishina 2009;Asamori et al 2010;Ichihara et al 2011).…”
Section: Resultssupporting
confidence: 78%
“…The distribution of conductor C6 and its resistivity (1 to 10 Ωm) are also consistent with the results of previous studies (Ogawa et al 1986;Ogawa 1987b). Recent wideband magnetotelluric profile measurements with site spacings of several kilometers have yielded more detailed images of the locations and depths of these conductors, although those images were limited to two-dimensions (Mitsuhata et al 2001;Ogawa et al 2001;Umeda et al 2006;Mishina 2009;Asamori et al 2010;Ichihara et al 2011).…”
Section: Resultssupporting
confidence: 78%
“…As underlined in Figure 7, the presence at shallow depths of the high conductive brine is probably responsible for a screen effect that makes detection of deeper conductive bodies difficult. Deep anomalies below a superficial conductive layer are detectable by the MT method in volcanic contexts [e.g., Whaler and Hautot , 2006; Umeda et al , 2006]. However, their detectability requires a large volume (several tens of km 3 ) of very conductive magma ( ρ < 10 ohm.m).…”
Section: Discussionmentioning
confidence: 99%
“…Deep anomalies below a superficial conductive layer are detectable by the MT method in volcanic contexts [e.g., Whaler and Hautot, 2006;Umeda et al, 2006]. However, their detectability requires a large volume (several tens of km 3 ) of very conductive magma (r < 10 ohm.m).…”
Section: Possible Deep (>3-4 Km) Magmamentioning
confidence: 99%
“…Another approach could be the combined use of geophysical (magnetotelluric and seismic interpretations) and petrologic (geothermobarometric constrains on the depth and nature of the magma chamber) methods (Pommier et al, 2010b). The perspective of the magnetotelluric studies was underlined by Umeda et al (2006) who indicated a crustal magma storage beneath the Iide Mts, Japan that was previously considered as a non-volcanic region.…”
Section: Introductionmentioning
confidence: 99%